Bronchial Anthracosis: A New Diagnosis for Benign Mass Lesions of the Lung - Mirsadraee, Majid (National Research Institute of Tuberculosis and Lung Disease, 2013)
BACKGROUND: This study aimed to identify the most important new radiological presentations of anthracosis and anthracofibrosis and evaluate the risk ratio for accurate diagnosis of these conditions using computed tomography instead of bronchoscopy. MATERIALS AND METHODS: This prospective, case-control study evaluated three groups of 70 patients with a bronchoscopic diagnosis of simple anthracosis and anthracofibrosis and 40 patients with a non-anthracotic diagnosis (control group). Bronchoscopy, chest radiographs and computed tomography (CT) (parenchymal and mediastinal windows) were reviewed. Special attention was given to mass lesions, calcified lymph nodes, bronchi and bronchial stenosis. RESULTS: Abnormal chest x-rays were observed in 93% of patients with bronchial anthracofibrosis; patchy consolidation was the most prevalent finding. The most significant CT finding was lymph node calcification (80%, odds ratio = 22.9), followed by bronchial calcification and bronchial stenosis (odds ratio = 6 and 2.91, respectively). Other significant findings were mass-like lesions (14%) and collapse (20%). CT findings were unremarkable in less than 1/6 of subjects. CONCLUSION: Lymph node and bronchial calcification can serve as accurate signs in diagnosing anthracosis of the lung. In addition, mass lesions, collapse and infiltration may be associated with a benign course.